Trends in Sieving and Its Applications in Cereals. A Literature Review - Sanchez-Suarez, Nevardo; Orozco-Mendoza, Gina Lia; Zartha-Sossa, Jhon Wilder; Gafaro-Garcés, Delcy Camila; Melchor-Cahuana, Lourdes Gladys; Gonzalez-Tovar, Cristian (Frontiers in Sustainable Food Systems, 2022)
In the agroindustry, sieving is a unit operation of great value, this work aims to make a review of the literature on sieving in cereals, a search equation was carried out in the Scopus database with the keywords sieve, screen, food process and cereal that resulted in 132 articles and 174 pa-tents, of the articles, 44 were directly related to sieving and 14 more had something to do with sieving, of the patents, in the last 10 years only 7 were directly related to sieving. To find new trends, raw materials and patent analysis, an information analysis table was built with name, year, author, keywords, countries, quartile, journal, relationship with the agro-industry and purpose. Among the most important conclusions, was the application of sieving in raw materi-als such as Rice, Corn, Wheat, Cotton, Millet, Quinoa, Almonds, Barley, Potato, Yucca, Microor-ganisms, Oats, Cotton, Protein, Peppers, Chia Seed, Furthermore, the use of rotating and vibrat-ing sieves was identified, as well as their positive effects on the physicochemical, standardiza-tion and classification of raw materials. The different types of equipment or methods focused on sieving that have been granted a use or design patent were also recognized.